2013
DOI: 10.1103/physreve.87.013302
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic model for microscale hydrodynamics and interfacial phenomena: Slip, films, and contact-angle hysteresis

Abstract: We present a model based on the lattice Boltzmann equation that is suitable for the simulation of dynamic wetting. The model is capable of exhibiting fundamental interfacial phenomena such as weak adsorption of fluid on the solid substrate and the presence of a thin surface film within which a disjoining pressure acts. Dynamics in this surface film, tightly coupled with hydrodynamics in the fluid bulk, determine macroscopic properties of primary interest: the hydrodynamic slip; the equilibrium contact angle; a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…The difference between Eq. In 2013, Colosqui et al [284] proposed a new fluid-solid interaction, which is composed of a repulsive core and an attractive tail Recently, Li et al [285] have conducted a comparative study between the   based interaction and the   based interaction at a high density ratio ( 500 lg  ). For liquid contact angles, it was found that the   based interaction works well for w 0 G  .…”
Section: The Contact Angle Treatmentmentioning
confidence: 99%
“…The difference between Eq. In 2013, Colosqui et al [284] proposed a new fluid-solid interaction, which is composed of a repulsive core and an attractive tail Recently, Li et al [285] have conducted a comparative study between the   based interaction and the   based interaction at a high density ratio ( 500 lg  ). For liquid contact angles, it was found that the   based interaction works well for w 0 G  .…”
Section: The Contact Angle Treatmentmentioning
confidence: 99%
“…Since the emergence of the pseudopotential LB model, there have been many studies of wetting phenomena using the model [12][13][14][15][16][17][18]. The first attempt was attributed to Martys and Chen in 1996 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Colosqui et al stressed that [18] their method is stable and robust within a range of moderate density ratios. The above-mentioned studies are related to the pseudopotential LB model.…”
Section: Introductionmentioning
confidence: 99%
“…41. The predictions of the proposed methodology are compared with the ones obtained from LB simulations.…”
Section: Wave-like Stripe Patterned Surface: Comparison With Mesoscopmentioning
confidence: 99%